Adat Basandi Syarak, Syarak Basandi Kitabullah: Understanding Local Wisdom in Social Studies Learning - Permata, Bunga Dinda (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2025)
This research explains the philosophy of